Activation of intestinal olfactory receptor stimulates glucagon-like peptide-1 secretion in enteroendocrine cells and attenuates hyperglycemia in type 2 diabetic mice. Issue 1 (December 2017) - Kim, Ki-Suk; Lee, In-Seung; Kim, Kang-Hoon; Park, Jiyoung; Kim, Yumi; Choi, Jeong-Hee; Choi, Jin-Sung; Jang, Hyeung-Jin
Abstract Odorants are non-nutrients. However, they exist abundantly in foods, wines, and teas, and thus can be ingested along with the other nutrients during a meal. Here, we have focused on the chemical-recognition ability of these ORs and hypothesized that the odorants ingested during a meal may play a physiological role by activating the gut-expressed ORs. Using a human-derived enteroendocrine L cell line, we discovered the geraniol- and citronellal-mediated stimulation of glucagon-like peptide-1 (GLP-1) secretion and elucidated the corresponding cellular downstream signaling pathways. The geraniol-stimulated GLP-1 secretion event in the enteroendocrine cell line was mediated by the olfactory-type G protein, the activation of adenylyl cyclase, increased intracellular cAMP levels, and extracellular calcium influx. TaqMan qPCR demonstrated that two ORs corresponding to geraniol and citronellal were expressed in the human enteroendocrine cell line and in mouse intestinal specimen. In a type 2 diabetes mellitus mouse model (db/db ), oral administration of geraniol improved glucose homeostasis by increasing plasma GLP-1 and insulin levels. This insulinotropic action of geraniol was GLP-1 receptor-mediated, and also was glucose-dependent. This study demonstrates that odor compounds can be recognized by gut-expressed ORs during meal ingestion and therefore, participate in the glucose homeostasis by inducing the secretion of gut-peptides.